(untitled) (Journal of Oriental Studies, 2023)
Waves of conquests, sweeping across Eurasia and devastating it, destroyed cultural wealth, including manuscripts, the surviving part of which was lost by time, and the other part is stored in different parts of the world. During the period of Soviet power, despite the development of science and technology in general, the history, culture, religion, and language of individual Soviet republics underwent strong fundamental changes. Nomadic culture was considered outside the written cultural heritage, sources in the original language, created by our compatriots in the Middle Ages, were not studied in the original, as a result, voids or incorrect information appeared on all the humanities of Kazakhstan. A huge part of the well-known Kipchak written monuments, made by medieval scientists in the Mamluk state in Egypt, dating back to the 13th-15th centuries, is still in the manuscript depositories of the Netherlands, Italy, France and Turkey. This is a complex of lexicographic and grammatical works, representing the primary source in the study of the history of modern Turkic languages, in particular Kazakh, the reconstruction of its phonetic, morphological and lexical systems. In this research, dedicated to the medieval manuscript of the 14th century “Kitab bulgat al-Mushtaq”, a comprehensive study is planned, consisting of the acquisition of the manuscript or the production of a copy, transfer to the archive and library fund of the Republic of Kazakhstan, translation and careful study of the lexical composition of the entire work. With an extended lexical analysis of the monument, where the vocabulary of the language will be formed, consisting of key words and terms, phrases and term combinations, stylistically colored words, words in a figurative sense, phraseological units, dialectisms, synonyms, homonyms, particles linking sentences, paragraphs, etc. The word-formation analysis will help to demonstrate the potential of the language, the possibilities of word formation, the most productive and active word-formation models of the Arabic and Mamluk-Kipchak languages. Keywords: Arabic, Mamluk-Kipchak, word formation, Ishtikak, medieval manuscript